Network structure of Japanese firms. Scale-free, hierarchy, and degree correlation: analysis from 800,000 firms - Tomohiko Konno (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
We analyze fundamental characteristics of the inter-firm transaction network through the data of 800,000 Japanese firms. We find that there exists a hierarchical structure and a negative degree correlation in this transaction network. We also find that this undirected network is a scale-free network. We bring to light these characteristics of the network and discuss why there is an important need to conduct research work on the actual network structure.
Keywords: L16; 330; Network of firms; scale-free network; complex network; hierarchy; degree correlation; Business Network; Lieferanten-Kunden-Beziehung; Wirtschaftskonzentration; Japan